ANALISIS FRAMING BERITA PEGAWAI PAJAK KORUPSI PADA SURAT KABAR KOMPAS.COM DAN DETIKFINANCE - Maura Frilicia Van Yusat; Hendra Setiawan (Kajian Linguistik dan Sastra, 2022)
The purpose of this study is to explain two different online-based newspaper media with the same news topic to find out the differences in the framing of the two news storiesusing the Zhongdang Pan and Gerald M. Kosicki model framing analysis approach which is divided into four parts, namely; syntax, script, thematic, and rhetorical. News must be based on facts, but each media has its own characteristics through news texts in an effort to lead opinion, display an impressive image, and the public needs to think critically. This research is a qualitative research with descriptive method. The online-based newspaper used are Kompas.com entitled “KPK Tetapkan 2 Pejabat Ditjen Pajak Tersangka Suap dan Gratifikasi” and DetikFinance entitled “Huft… Gaji Pegawai Pajak Hampir Ratusan Juta tapi Masih Korupsi Juga”, the two media have different characteristics in convey news so that it can be seen more efficiently which one is a role model in writing news texts. The topics chosen are according to the 2021 publication year with a discussion of corruption cases by tax officials. The result of the research that can be seen are that the Kompas.com media is more suitable as a role model in news writing because it chooses words that are selective and professional. Meanwhile, DetikFinance media involves gimmicks in news writing which is published as a public attraction. It is known, the delivery of news needs to be serious in an professional manner without sensation.